(untitled) (Research, Society and Development, 2021)
The aim of the present study was to describe the temporal trend of the reported cases of gestational and congenital syphilis in residents of medium-sized cities in the State of Paraná between 2007 and 2017. This is a descriptive and analytical epidemiological study of time series type with secondary data obtained in the DATASUS of the SINAN Net and the SINASC. To verify the rate trend of syphilis detection in pregnant women and the incidence rate of congenital syphilis, a mixed effects model with random effect in the intercept and also in the inclination was adjusted. Negative Binomial Regression and the Maximum Likelihood method were also used. There was a significant influence of time on the rate of syphilis detection in pregnant women and on the incidence rate of congenital syphilis, with an increase each year of 31% (IC 95% 23-39, p <0.001) and 25% (IC 95% 17-34, p <0.001) in the rates, respectively. Most municipalities presented a growing trend in syphilis rates in pregnant and congenital. Given this, it is necessary to adopt intervention measures to change the reality presented.